2015
DOI: 10.1016/j.jgeb.2014.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of buffalo interleukin 8 (IL-8) and its expression in endometritis

Abstract: River buffalo (Bubalus bubalis bubalis) with a population over 135 million heads is an important livestock. Interleukin 8 (IL-8) is a member of the chemokine family and is an important chemoattractant for neutrophils associated with a wide variety of inflammatory diseases such as endometritis. Tissue samples from the mammary gland, uterus and ovary were obtained from river buffalo (Mediterranean type) with and without endometritis. Bacteriological examination showed the presence of both gram positive and negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
2
3
0
Order By: Relevance
“…IL-8 is an important mediator for innate immunity in mammals and involved in recruitment and activation of different leukocytes through modulating cytokine production ( Min et al., 2001 ). Similar findings were reported in another study, where IL8 was up-regulated significantly (P < 0.0159) to 26.6 fold in uterine tissue of buffaloes with endometritis when compared to the healthy uterine tissue ( Mossallam et al., 2015 ). The current study showed higher expression of IL-8 mRNA in CS group compared to all other groups studied, which may be due to the presence of bacterial secretory components in excess that increases the possibility of IL-8 signalling to attract neutrophils to the area of infection.…”
Section: Discussionsupporting
confidence: 90%
“…IL-8 is an important mediator for innate immunity in mammals and involved in recruitment and activation of different leukocytes through modulating cytokine production ( Min et al., 2001 ). Similar findings were reported in another study, where IL8 was up-regulated significantly (P < 0.0159) to 26.6 fold in uterine tissue of buffaloes with endometritis when compared to the healthy uterine tissue ( Mossallam et al., 2015 ). The current study showed higher expression of IL-8 mRNA in CS group compared to all other groups studied, which may be due to the presence of bacterial secretory components in excess that increases the possibility of IL-8 signalling to attract neutrophils to the area of infection.…”
Section: Discussionsupporting
confidence: 90%
“…The observed elevation in IL-8 levels augmented the elevation of TNF-α that induced its production and further uterine PMNs chemotaxis (Manimaran et al, 2016;Nehru et al, 2019). Similar findings were obtained by Mossallam et al (2015) who recorded significant increase in the IL-8 levels in uterine tissue of SCE buffaloes. Furthermore, Singh (2017) observed increments in both circulating and endometrial IL-8 levels in SCE buffaloes when compared to control group.…”
Section: Discussionsupporting
confidence: 82%
“…Tumor necrosis factor alpha, multifunctional pro-inflammatory cytokine, secreted by many cells as macrophages, T lymphocytes and ovarian granulosa cells (Price and Sheldon, 2013). Interleukine-8, the primary neutrophil chemokine, is produced by activated leukocytes that enhance the targeted release of neutrophils and T lymphocytes in order to eliminate pathogens in bovine uterus (Bhadaniya et al, 2019;Mossallam et al, 2015). Both TNF-α and IL-8 are essential in uterine immune cascade of SCE buffaloes via their upregulation in the endometrium (Loyi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…IL‐8 is a proinflammatory chemokine that regulates recruitment and trafficking of neutrophils (Neuman et al, ). The expression of IL‐8 was detected in mammary glands, uteri, and ovaries of buffalo with and without inflammation (Abou Mossallam, El Nahas, Mahfouz, & Osman, ). Moreover, IL‐8 was found in the preovulatory follicle, and its role in folliculogenesis was reported (Gazvani et al, ).…”
Section: Discussionmentioning
confidence: 99%